FRAMING PEMBERITAAN PENYELENGGARAAN ANGKUTAN BARANG UMUM DI PROVINSI SULAWESI TENGGARA DALAM MEDIA ONLINE - Maudhy Satyadharma; La Ode Muhamad Nurrakhmad Arsyad; Try Sugiyarto Soeparyanto; Hado (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The Reporting by the mass media is able to influence public perception and opinion regarding an event. Research was carried out to analyze the framing of news on the Implementation of Public Goods Transport including Heavy Equipment on the Local Media Telisik.Id in the news in November 2023. using Entman's framing analysis with four things, namely Define Problems, Diagnose Cause, Make Moral Judgment and Treatment Recommendation. Conclusion of the research carried out by finding the online media Telisik.id framing it and seeing that the Southeast Sulawesi Provincial Transportation Service has made continuous and consistent efforts in controlling and supervising Public Goods Transportation activities in accordance with applicable regulations to minimize violations and errors that could result in traffic accidents and potentially resulting in loss of life and in order to create safe, comfortable, secure and sustainable transportation